Pengambilan Keputusan Khalifah Umar Bin Khattab dalam Pemberian Tunjangan Wajib - Pradesa, Dedy (STID Al Hadid Surabaya, 2024)
THE DECISION MAKING OF UMAR BIN KHATTAB CALIPH IN PROVIDING MANDATORY GRANTS. This study examines Caliph Umar bin Khattab's decision making in providing mandatory grants and establishing diwan institutions. During Umar's caliphate, he faced many new situations as a result of the expansion of Islamic territory, which gave rise to problems and required the caliph to make decisions. One of them is related to the amount of wealth that goes to the Caliphate. The focus of this study's problem is how Caliph Umar's decision-making process in this case was approached within the framework of a decision-making system. Decision making systems refer to input, process, and output. This study used qualitative methodology with related historical literature data sources. The results of the study showed that in making decisions, Umar based the problem input data and the context of the war situation. Decision making process starts from problem diagnosis, determining criteria and targets as a basis, developing alternatives, selecting, evaluating and determining the best alternative. In the process, Umar involved other members of the organization for deliberation and proposed solutions. As an output, Umar established wealth management in a new way, namely in the form of mandatory grants for Islamic troops and their families, as well as those who had fought previously. The list of recipients of grants with different amounts is based on their contribution and relationship with the Prophet. The list is managed in an institution called diwan.